The writings of the Soviet Union in the chronicles El viaje by Luis Spota (Anclajes, 2023)
The chronicles of the Mexican writer Luis Spota published in the Joaquín Mortiz editorial in 1973 under the title of El viaje recount the Soviet experience during the presidential tour of Luis Echeverría. The text is structured from the journalist's experiences in the Soviet Union. The reading keys focus on the analysis of the testimonies offered by the work in contrast to the critical assessment of some references to the geography and history of the Eastern European country with the identity of the Mexican writer.
Keywords: Luis Spota; chronicle; Soviet Union; Luis Echeverría